Environmentally oriented business management - the main principle of the orientation transition to a model of sustainable development and improved quality of life. (Journal of Economic Research & Business Administration, 2015)
In the article the necessity of establishing an environmental management system at domestic enterprises. The classification of types of business management based on their activities and performance of environmental policy.